2007
DOI: 10.1007/s11082-007-9115-3
|View full text |Cite
|
Sign up to set email alerts
|

Performance of an optical wideband WDM system considering stimulated Raman scattering, fiber attenuation and chromatic dispersion

Abstract: The performance of an optical wideband wavelength division multiplexed (WDM) communication system is analyzed considering the effects of stimulated Raman scattering, fiber attenuation and chromatic dispersion. Improved models for the Raman gain and the fiber attenuation constant are proposed, which yield better and reliable performance results of the WDM system. Effect of fiber chromatic dispersion is also investigated and it is observed that dispersion can suitably be selected to overcome the limitations impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…1 Similar oscillatory behavior is observed for other choices of the initial amplitudes. Figure 1 (b) shows the phase portrait for the system (13). Since all trajectories are closed curves we conclude that the dynamics is indeed periodic and that the equilibrium state is stable.…”
Section: B Equilibrium States Stability and Conserved Quantitiesmentioning
confidence: 77%
See 1 more Smart Citation
“…1 Similar oscillatory behavior is observed for other choices of the initial amplitudes. Figure 1 (b) shows the phase portrait for the system (13). Since all trajectories are closed curves we conclude that the dynamics is indeed periodic and that the equilibrium state is stable.…”
Section: B Equilibrium States Stability and Conserved Quantitiesmentioning
confidence: 77%
“…Early studies of Raman crosstalk in WDM transmission focused on the dependence of the energy shifts on the total number of channels [3], as well as on the impact of energy depletion [5] and group velocity dispersion [12,13] on the dynamics. Later on attention turned to the combined effects of Raman crosstalk and bit-pattern randomness in the on-off-keying (OOK) transmission scheme, and it was found that the probability density function (PDF) of the pulse amplitudes is lognormal [4,6,10,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…However, the transmission of photons through an optical fiber reduces the power of the signal. This is known as the attenuation coefficient [129] of the fiber α (wavelength-dependent and expressed in dB/km) and it is calculated with the following expression:…”
Section: Optical Mediummentioning
confidence: 99%
“…For inelastic scattering, we focus on Raman scattering 3 [131,132,129,133]. Although the amount of signal scattered is much smaller than Rayleigh, it covers a broad spectrum.…”
Section: Scatteringmentioning
confidence: 99%